Development and optimization of a mechlorethamine topical formulation utilizing a model drug bridging strategy and quality by design - Hemil Shah; Prachi Pandey; Priyal Patel (Journal of Applied Pharmaceutical Research, 2026)
Background: This study aimed to develop a stable, clinically suitable topical mechlorethamine formulation using Quality by Design (QbD) principles to address chemical instability and cytotoxicity. The objectives were to establish a data-driven formulation design space, identify critical material attributes, and apply a surrogate active pharmaceutical ingredient (API) approach to ensure biological performance while enabling safe early-stage optimization. Methodology: A 2³ full factorial Design of Experiments (DOE) was employed to evaluate the effects of ethanol, isopropyl myristate (IPM), and Carbopol 974P on assay concentration, viscosity, and pH. Regression modeling and response surface analysis were used to define the formulation design space. Diclofenac sodium was used as a surrogate API to study matrix behavior prior to the incorporation of mechlorethamine. The optimized formulation was subjected to long-term, refrigerated, and accelerated stability studies. Results and Discussion: Carbopol 974P concentration was identified as the primary factor influencing viscosity, while assay concentration and pH remained stable across the design space. The optimized formulation (73% ethanol, 3% IPM, and 0.12% Carbopol 974P, pH 5.5) met all Quality Target Product Profile criteria. Bridging studies demonstrated comparable physicochemical properties between surrogate and mechlorethamine-loaded formulations, indicating excipient-driven performance. Under ICH stability conditions, the optimized formulation retained 98.3% assay after 3 months at 40°C/75% RH (0.9% loss), with total impurities remaining at 0.19% (NMT 0.5%), stable viscosity (40–60 cps), controlled pH (5.51–5.53), and no physical instability. Conclusion: The QbD-driven approach enabled the development of a stable, reproducible, and biologically effective topical mechlorethamine formulation suitable for scale-up and regulatory advancement.